The Implementation of Organization Development at PT Pembangkitan Jawa-Bali - Puri Handoko (JURNAL MANAJERIAL, 2021)
Background – PT Pembangkitan Jawa-Bali (PT PJB) is a subsidiary of PT PLN (Persero) which participates in the Business Performance Rating Program in Environmental Management (PROPER) organized by the Ministry of Environment and Forestry (MoEF) of the Republic of Indonesia based on Ministry of Environment Regulation No 06 year 2013. As a subsidiary of PT PLN (Persero), PT PJB establishes management contracts which aim to get a Gold PROPER rating from the MoEF. Even so, the company still has some challenges as it encounters several problems of managing CSR internally. As a first step, PT PJB, especially in CSR Department, has made improvements in its organization by implementing a PROPER-based performance appraisal system in managing CSR in all PT PJB Power Plants. Purpose – Examining the phenomenon which has been occurring for the past several years, researcher decided to conduct observations and interviews. This study tries to explain descriptively how changes have been designed and implemented through the "Performance Management Model" approach. Design / Methodology / Approach – This study is a qualitative field research. The data for this research were collected through observation and interviews. Focus interview were about CSR concept, Company’s goal and target, integrated CSR management to Company’s vision and mission, CSR management problems in different area, and social-environment national issue. Data collected were then analyzed using content analysis method. Result and Discussion – Positive impacts were found after the implementation of change in management model at the CSR Department, such as maturity level in CSR management increased, charity program decreased, and human resources capability increased. The result that One of the company’s Power Plants, Paiton Power Plant, won the Gold PROPER rating. It could be considered as the biggest achievement since the company became the only power plant in the PLN (Persero) Group which first obtained a Gold PROPER rating. Conclusion – The establishment and implementation of PROPER-based governance system would not be optimum if it did not involve employees (Head Department, Managers, Supervisors, and staff) mastering in CSR. Research Limitations – This study has limitations in reference, namely the limited researches and previous journals on organizational change, particularly in the management of its CSR activities, which researcher found as reference material.